THE NURSE'S HUMANISTIC FUNCTIONING IN RELATION TO THE PAIN OF THE CHILD PATIENT WITH BURNS - Danelia Gómez-Torres; Victoria Maldonado-González; Berenice Reyes-Robles; Ana Laura Muciño Carrera (Universidade Federal do Paraná, 2014)
This article aims to reflect on the humanistic functioning of the nurse in the interventions with nociceptive, somatic pain in children. To this end a qualitative descriptive study was undertaken, directed and discussed in accordance with Husserlian phenomenology. Ethical-legal aspects were taken into consideration, interviews being held with 10 nurses who are specialists in the area of burns. The relevant data were selected through the colorimetric technique, so as to later undertake content analysis. The results revealed the nurse to be a professional who acts affectively in situations of distress and sadness, protecting the child patient empathetically. In addition, it is possible to perceive that non-pharmacological therapies, such as play therapy, laughter therapy, music therapy, relaxation exercises, breathing exercises, and psychological support are coadjuvant in combating pain. At the end of the study, it is reflected that the nurse's intervention is highly humanistic, and it is shown that pain must be treated by professionals with great sensitivity, so as to promote highly humane care.